Sisŏn nŏmŏ If you were me 5 - Kang, I-kwan.; Pu, Chi-yŏng.; Kim, Tae-sung.; Yun, Sŏng-hyŏn; Sin, Tong-il.; Kim, Hyŏn-ju; Pak, Chŏng-uk.; Yi, Chŏng-ŭn.; Kim, Chin-gŭn; Sim, I-yŏng.; Kukka Inkwŏn Wiwŏnhoe; Indie Story; et al. (Sŏul : DS Media, 2012)
"If You Were Me 5 is an innovative omnibus film project to promote tolerance and human rights and shed light on the hardships disadvantaged people face in Korea."---YesAsia.
Ippal tugae / kamdok, Kang I-kwan
Nima / kamdok, Pu Chi-yŏng
Pengmun pektap / kamdok, Kim Tae-sung
Banana sweikŭ / kamdok, Yun Sŏng-hyŏn
Chinsil ŭl wihayŏ / kamdok, Sin tong-il.
Originally produced as a motion picture in 2011.
aKamdok, Kang I-kwan, Pu Chi-yŏng, Kim Tae-sung, Yun Sŏng-hyŏn, Sin Tong-il.
DVD; Dolby Digital 5.1, NTSC all regions.
In Korean with optional subtitles in Korean and English.
Keywords: Human rights -- Korea (South) -- Drama; Feature films -- Korea (South).; Feature films; Fiction films